2010
DOI: 10.1124/mol.109.062463
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Corticotropin-Releasing Factor Receptor-1 Antagonists on the Brain Stress System Responses to Morphine Withdrawal

Abstract: The role of stress in drug addiction is well established. The negative affective states of withdrawal most probably involve recruitment of brain stress neurocircuitry [e.g., induction of hypothalamo-pituitary-adrenocortical (HPA) axis, noradrenergic activity, and corticotropin-releasing factor (CRF) activity]. The present study investigated t$he role of CRF receptor-1 subtype (CRF1R) on the response of brain stress system to morphine withdrawal. The effects of naloxone-precipitated morphine withdrawal on norad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 35 publications
9
53
0
Order By: Relevance
“…Data are expressed as the mean±SEM (n=4-6), ***p<0.001 versus morphine (mor)+saline (sal); +++ p<0.001 versus sal+naloxone (nx); && p<0.01, &&& p<0.001 versus wild-type mice mice showed less diarrhea and motor activity. These findings are consistent with a previous report from our laboratory (Navarro-Zaragoza et al 2010) showing that CP-15426 or antalarmin (CRF1R antagonists) decreased the weight loss and the irritability observed in morphine withdrawn rats.…”
Section: Discussionsupporting
confidence: 95%
“…Data are expressed as the mean±SEM (n=4-6), ***p<0.001 versus morphine (mor)+saline (sal); +++ p<0.001 versus sal+naloxone (nx); && p<0.01, &&& p<0.001 versus wild-type mice mice showed less diarrhea and motor activity. These findings are consistent with a previous report from our laboratory (Navarro-Zaragoza et al 2010) showing that CP-15426 or antalarmin (CRF1R antagonists) decreased the weight loss and the irritability observed in morphine withdrawn rats.…”
Section: Discussionsupporting
confidence: 95%
“…However, the failure of CRH antagonists in our study to alter the nicotine-stimulated secretion of corticosterone was not due to the choice of the dose of these antagonists because both antagonists clearly blocked the effect of CRH and these doses have been used previously (Deak et al . 1999, Navarro-Zaragoza et al . 2010, Gulyas et al .…”
Section: Discussionmentioning
confidence: 99%
“…CRF signaling is mediated through the activities of two distinct G-protein coupled receptor subtypes, known as CRF-R1 and CRF-R2 [24], [25]. Indeed, studies have demonstrated the ability of CRF receptor antagonists in reducing negative motivational effects during withdrawal phase [26], [27]. The attenuation of aversive effects of opiate withdrawal in CRF-R1 and CRF-R2 deficient mice further validates the role of the CRF pathway in addiction and withdrawal [28], [29].…”
Section: Introductionmentioning
confidence: 85%